Cerebrovascular Response to Propofol, Fentanyl, and Midazolam in Moderate/Severe Traumatic Brain Injury: A Scoping Systematic Review of the Human and Animal Literature - Logan Froese; Joshua Dian; Carleen Batson; Alwyn Gomez; Bertram Unger; Frederick A. Zeiler (Neurotrauma Reports, 2020)
Intravenous propofol, fentanyl, and midazolam are utilized commonly in critical care for metabolic suppression and anesthesia. The impact of propofol, fentanyl, and midazolam on cerebrovasculature and cerebral blood flow (CBF) is unclear in traumatic brain injury (TBI) and may carry important implications, as care is shifting to focus on cerebrovascular reactivity monitoring/directed therapies. The aim of this study was to perform a scoping review of the literature on the cerebrovascular/CBF effects of propofol, fentanyl, and midazolam in human patients with moderate/severe TBI and animal models with TBI. A search of MEDLINE, BIOSIS, EMBASE, Global Health, SCOPUS, and the Cochrane Library from inception to May 2020 was performed. All articles were included pertaining to the administration of propofol, fentanyl, and midazolam, in which the impact on CBF/cerebral vasculature was recorded. We identified 14 studies: 8 that evaluated propofol, 5 that evaluated fentanyl, and 2 that evaluated midazolam. All studies suffered from significant limitations, including: small sample size, and heterogeneous design and measurement techniques. In general, there was no significant change seen in CBF/cerebrovascular response to administration of propofol, fentanyl, or midazolam during experiments where PCO2 and mean arterial pressure (MAP) were controlled. This review highlights the current knowledge gap surrounding the impact of commonly utilized sedative drugs in TBI care. This work supports the need for dedicated studies, both experimental and human-based, evaluating the impact of these drugs on CBF and cerebrovascular reactivity/response in TBI.